Real evapotranspiration and transpiration through a tropical rain forest in central Amazonia as estimated by the water balance method - Leopoldo, Paulo Rodolfo [UNESP]; Franken, Wolfram Karl; Villa Nova, Nilson Augusto (Elsevier, 1995)
The research was carried out from January 1981 to December 1983, in a small watershed of 1.3 km2 surface area located at INPA's Ducke Forest Reserve. This watershed is drained by the Barro-Branco stream, and its vegetation cover is characterized by a typical tropical rain forest of the central Amazon region. In order to estimate its real evapotranspiration, transpiration and other hydrological parameters, the precipitation and the discharge yielded by the Barro-Branco stream were measured during the experimental period. A mean precipitation of 2209 mm year-1 was recorded, from which 67.6% was lost to the atmosphere through evapotranspiration. This result was similar to that calculated by the modified Penman's method (1479.2 mm year-1). If the average rain water interception by the forest canopy is assumed to be 11.3% of the total precipitation amount, as estimated by Gash's model, the transpiration was 1243.7 mm year-1, representing 56.3% of the total rainfall observed for the 1981-1983 period. © 1995.
Keywords: Evapotranspiration; Transpiration; Tropical rain forest; Water balance method; Watershed